Daphnia magna modifies its gene expression extensively in response to caloric restriction revealing a novel effect on haemoglobin isoform preference. Issue 17 (30th July 2020) - Hearn, Jack; Clark, Jessica; Wilson, Philip J.; Little, Tom J.
Abstract: Caloric restriction (CR) produces clear phenotypic effects within and between generations of the model crustacean Daphnia magna . We have previously established that micro‐RNAs and cytosine methylation change in response to CR in this organism, and we demonstrate here that CR has a dramatic effect on gene expression. Over 6, 000 genes were differentially expressed between CR and well‐fed D. magna, with a bias towards up‐regulation of genes under caloric restriction. We identified a highly expressed haemoglobin gene that responds to CR by changing isoform proportions. Specifically, a transcript containing three haem‐binding erythrocruorin domains was strongly down‐regulated under CR in favour of transcripts containing fewer or no such domains. This change in the haemoglobin mix is similar to the response to hypoxia in Daphnia, which is mediated through the transcription factor hypoxia‐inducible factor 1, and ultimately the mTOR signalling pathway. This is the first report of a role for haemoglobin in the response to CR. We also observed high absolute expression of superoxide dismutase (SOD) in normally fed individuals, which contrasts with observations of high SOD levels under CR in other taxa. However, key differentially expressed genes, like SOD, were not targeted by differentially expressed micro‐RNAs. Whether the link between haemoglobin and CR occurs in other organisms, or is related to the aquatic lifestyle, remains to be tested. It suggests that one response to CR may be to simply transport less oxygen and lower respiration.